The concept of the animal and modern theories of art - Grén, Roni, author.
1 online resource (x, 164 pages)
Keywords: "This book examines the importance of the animal in modern art theory, using classic texts of modern aesthetics and texts written by modern artists to explore the influence of the human-animal relationship on nineteenth and twentieth century artists and art theorists. The book is unique due to its focus on the concept of the animal, rather than on images of animals, and it aims towards a theoretical account of the connections between the notions of art and animality in the modern age. Roni Grén’s book spans various disciplines, such as art theory, art history, animal studies, modernism, postmodernism, posthumanism, philosophy, and aesthetics."--Provided by publisher.